Dinosaur - Benton, M. J. (London Kingfisher Books, 1991)
Surveys the world of prehistoric life before and after the dinosaurs and gives alphabetically arranged descriptions of dinosaur species, from Acanthopholis to Zephyrosaurus.
Include Illustrations and Index
Keywords: Dinosaurs